Linkage of TNF genes to the HLA-B locus. - Inoko, H (1987)
Pulsed field gel electrophoresis was used to determine the location of the tumour necrosis factor (TNF) alpha and beta genes. They were shown to be linked to the HLA-B locus; analogous to their location in mouse, between the complement (class III) region and H-2D. However, the distance between the TNF genes and the class I region was much greater in man, namely about 260 kb, compared to 70 kb in the mouse. This finding may have implications for some HLA associated diseases.